A Framework Of Knowledge Management For Higher Education Business Incubation - Hennessy, Philip (Journal of Knowledge Management Practice, 2012)
This paper investigates the link between the management of knowledge in Higher Education incubation and the growth of the firm. The development of Higher Education Institute (HEI) incubation has become a popular policy in many parts of the world and is viewed as a tool for promoting entrepreneurship and economic growth. This paper adds to the research on Higher Education incubation by proposing a strategic approach to incubation firm growth. While new knowledge is developed by individuals, the new firm and the Higher Education Institute play a critical role in articulating and amplifying that knowledge. This paper reviews the role of Higher Education business incubation. It reviews Penrose’s Theory of The Growth of the Firm. It then synthesises knowledge management literature and describes a strategic approach to designing knowledge initiatives to achieve an “impregnable base” for firm growth.